Evaluation of the toxicity of a propolis extract on Varroa destructor (Acari: Varroidae) and Apis mellifera (Hymenoptera: Apidae) - Damiani, Natalia (2010)
The effects of a propolis extract on Varroa destructor and Apis mellifera were evaluated by three different application methods: topical, spraying and oral. A propolis sample was extracted and its organoleptic and physic-chemically traits characterized. These analyses showed that it was a typical propolis from the Pampean region in Argentina, with elevated contents of biologically active compounds. Topical application was carried out by subjecting mites to contact with various propolis concentrations for different periods of time, which resulted in mortality and narcosis. Acaricidal effects were stronger with increasing concentrations of the propolis extracts. Spraying infested bees with a 10% propolis solution was harmless for bees but killed 78% of mites. Feeding infested bees with propolis extract in sugar syrup was not toxic to the mites but caused the death of bees treated with the highest concentration. Our results suggest that the propolis extracts from the Pampean Region could be incorporated into bee colonies by spraying, although the appropriate doses and concentrations to be administered, and the mechanism of action of the extracts on the mites are still to be elucidated.